Pengaruh Pengetahuan, Kemampuan, Dan Pengalaman Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada Perusahaan Rokok Sekar Anom Di Kabupaten Pamekasan) - Al Ja’fari, Ach Shohibul Risqi; Wahono, Budi; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to describe the performance, knowledge, ability, and work experience simultaneously and partially at P.R Sekar Anom. This study uses explanatory research with a quantitative approach method. Explanatory research. The population of this study were all employees at P.R Sekar Anom, totaling 63 people. The sampling technique used a saturated sampling technique on 63 employees at P.R Sekar Anom because there were less than 100 respondents. The results of the study showed that knowledge, ability and experience simultaneously and partially had a significant effect on employee performance at P.R Sekar Anom. Keywords: Knowledge, Ability, Experience, And Employee Performance